1988
DOI: 10.1111/j.1432-1033.1988.tb13834.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of neutral oligosaccharides derived from respiratory‐mucus glycoproteins of a patient suffering from bronchiectasis, determined by combination of 500‐MHz 1H‐NMR spectroscopy and quantitative sugar analysis

Abstract: Carbohydrate chains of respiratory‐mucus glycopeptides from a patient (blood group O) suffering from bronchiectasis with a Kartagener's syndrome have been released by alkaline borohydride treatment. Application of high‐performance liquid chromatography using subsequently two silica columns, one bonded with aminopropyl groups and the other with octadecyl groups, afforded 39 neutral fractions; 35 oligosaccharide‐alditol structures have been characterized by employing 500‐MHz 1H‐NMR spectroscopy in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…They have reported that the MR spectral characteristics, in particular the chemical shift, alter according to the type of oligosaccharide in which the fucose is incorporated . They have also described how the chemical shifts of these fucose entities can alter with changes to the microenvironment , such as pH. The spectral characteristics are consistent with several of those assigned in the cell models.…”
Section: Introductionmentioning
confidence: 55%
“…They have reported that the MR spectral characteristics, in particular the chemical shift, alter according to the type of oligosaccharide in which the fucose is incorporated . They have also described how the chemical shifts of these fucose entities can alter with changes to the microenvironment , such as pH. The spectral characteristics are consistent with several of those assigned in the cell models.…”
Section: Introductionmentioning
confidence: 55%
“…It cannot be invoked for the fucose in b conformation as this molecule is only present in mammals in GDP-fucose and/or in free fucose and not in fucose bound to other residues. Either the presence of free fucose or a restricted On the other hand, the intensity of the fucose signal at 4.28 ppm, corresponding to a fucose bound to Gal (54,55,57), increases after the Golgi pH increase by NH 4 Cl treatment (Table 3). Distribution of fucosyltransferase has been the object of studies in relation to Lewis antigen synthesis by concluding that its alteration is mainly attributable to Golgi subcompartments (63).…”
Section: H-mrs Can Detect Aberrant Glycosylation In Hela Cellsmentioning
confidence: 93%
“…According to current literature (54)(55)(56)(57)(58)(59), the chemical shift of the H5 proton points to fucose moiety differently bound in an oligosaccharide chain. The rather low-field resonance of aFuc2 and aFuc3 reported in Table 2 …”
Section: H-mrs Can Detect Aberrant Glycosylation In Hela Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mucin glycans can be classified into three groups of increasing acidity: neutral, sialylated, and sulfated (22,(36)(37)(38). To date, over 100 mucin oligosaccharides have been identified, including 81 from one subject alone (22,37,(39)(40)(41).…”
Section: Carbohydate Contentmentioning
confidence: 99%